Civic Learning through active citizenship in diverse societies - Brigitte Kukovetz; Annette Sprung; Petra Wlasak (European Journal for Research on the Education and Learning of Adults, 2025)
In response to the growing heterogenous populations in urban areas, and the important role of civic engagement and active citizenship for the promotion of democratic processes, this paper discusses the active participation of resident foreign citizens and/or persons with a history of migration, in urban areas. The theoretical connections between active citizenship, lived citizenship and civic learning are outlined and then linked with the results of an applied research project focused on various aspects of gender. In conclusion, active – lived – citizenship, in particular ‘performative’ acts of citizenship, generate civic learning as subjectification. Public spaces as learning opportunities for active engagement should take into account aspects of diversity as well as inequalities in a diverse society in order to promote inclusion and democracy for as many residents as possible regardless of their citizenship status.